KOMUNIKASI ANTARETNIK DALAM MASYARAKAT TUTUR DIGLOSIK: Kajian Etnografi Komunikasi Etnik Using - Imam Suyitno (Humaniora, 2006)
People need communication in their daily activities. The term cross cultural communication is used to refer to communication conducted by people of different culture. This type of communication normally occurs in a diglosic community where two or more ethnic groups live together. In conducting communication, each of the ethnic group will apply and share their language and socio-cultural norms accepted by each other. All participants of communication are tied by rules that live in the speech community. Although they attempt to obey the norms, culturally the characteristic of each ethnic is still observed at the verbal attitude of their speech. In this case, we can observe the characteristic of speech act usage when speaking to other etnics, especially to Javanese and Madurese. Some factors which influence the etnic groups to choose the verbal attitude are a social distance, power, social variable, and cultural values.